2016
DOI: 10.3892/ol.2016.4354
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance confocal microscopy and dermoscopy for in vivo, non-invasive skin imaging of superficial basal cell carcinoma

Abstract: Superficial basal cell carcinoma (sBCC) is the second most frequent histological type of basal cell carcinoma (BCC), usually requiring a skin biopsy to confirm the diagnosis. It usually appears on the upper trunk and shoulders as erythematous and squamous lesions. Although it has a slow growth and seldom metastasizes, early diagnosis and management are of crucial importance in preventing local invasion and subsequent disfigurement. Dermoscopy is nowadays an indispensable tool for the dermatologist when evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 21 publications
0
38
0
1
Order By: Relevance
“…However, a study that focused on the immunogenicity of the quadrivalent human papillomavirus vaccine found that it is highly efficient in men aged from 16 to 26 years, with seroconversion within 7 months, with antibodies being detected even at 36 months, numbers comparable with those encountered in clinical trials conducted in female patients (51). In a study conducted by Giuliano et al (52) similar results regarding the efficacy of the quadrivalent HPV vaccine against HPV infection in male patients were found (53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Prevention Of Hpv Infection In Menmentioning
confidence: 70%
“…However, a study that focused on the immunogenicity of the quadrivalent human papillomavirus vaccine found that it is highly efficient in men aged from 16 to 26 years, with seroconversion within 7 months, with antibodies being detected even at 36 months, numbers comparable with those encountered in clinical trials conducted in female patients (51). In a study conducted by Giuliano et al (52) similar results regarding the efficacy of the quadrivalent HPV vaccine against HPV infection in male patients were found (53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Prevention Of Hpv Infection In Menmentioning
confidence: 70%
“…The current study primarily aimed to assess the accuracy, sensitivity and specificity of RCM in the diagnostic of subclinical AKs after 5‐FU treatment. RCM has been previously described for evaluation of non‐melanoma skin cancer; most studies are related to assessment of basal cell carcinoma . Studies addressing the application of this method for actinic keratosis are still scarce in literature.…”
Section: Discussionmentioning
confidence: 99%
“…RCM has been previously described for evaluation of non-melanoma skin cancer; most studies are related to assessment of basal cell carcinoma. [49][50][51] Studies addressing the application of this method for actinic keratosis are still scarce in literature. Ulrich et al described the use of RCM in AK follow-up after imiquimod treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biopsy can be traumatic and risky, especially for elderly patients, because of poor wound healing and possibility of infection . Therefore, several noninvasive imaging modalities have been developed to enhance the diagnosis of skin diseases . Among several different modalities, optical coherence tomography (OCT) stands out.…”
Section: Introductionmentioning
confidence: 99%